Days of grace : a memoir - Ashe, Arthur; Rampersad, Arnold (New York : Alfred A. Knopf, 1993)
Biography of the tennis player and social activist who died of AIDS in 1993.
Includes index.
Keywords: Ashe, Arthur; Tennis players -- United States -- Biography; AIDS (Disease) -- Patients -- Biography